2017
DOI: 10.2147/opth.s127943
|View full text |Cite
|
Sign up to set email alerts
|

The role of serum apelin in retinopathy of prematurity

Abstract: ObjectiveTo evaluate the role of serum apelin as a diagnostic tool in retinopathy of prematurity (ROP) disease.Patients and methodsThirty-eight preterm infants (60% male) with gestational age ranging from 30 to 36 weeks admitted to the neonatal intensive care unit, KJO Hospital, Saudi Arabia with proven diagnosis of ROP were included in the study. In addition, 27 preterm infants without ROP served as controls. All newborn infants in the study were subjected to adequate history taking, full clinical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…Several serum/plasma factors including VEGF, 145,163,198,223,300,303,427 bilirubin, 96,113,134,169,178,201,258,416 sE-selectin, 66,304 CRP, 186 apelin, 16 vitamin D, 194 trace elements such as zinc, 407 and inflammatory cytokines such as IL-6 350 have been studied. Although VEGF is a key factor in retinal angiogenesis, studies on systemic levels of VEGF and related factors such as soluble VEGF receptors showed contradictory results.…”
Section: Alternative Risk Factorsmentioning
confidence: 99%
“…Several serum/plasma factors including VEGF, 145,163,198,223,300,303,427 bilirubin, 96,113,134,169,178,201,258,416 sE-selectin, 66,304 CRP, 186 apelin, 16 vitamin D, 194 trace elements such as zinc, 407 and inflammatory cytokines such as IL-6 350 have been studied. Although VEGF is a key factor in retinal angiogenesis, studies on systemic levels of VEGF and related factors such as soluble VEGF receptors showed contradictory results.…”
Section: Alternative Risk Factorsmentioning
confidence: 99%
“…13 The occurrence of thrombocytopenia (OR: 2, CI: 0.6-6.5) 16 is another significant risk factor for development of ROP, in addition to neonatal apnea (OR: 15.6, CI: 8-30.2) and phototherapy for jaundice (OR: 2.1, CI: 1.2-3.7). 17…”
Section: Reported Anmentioning
confidence: 99%
“…Concurrently, animal studies on retinal endothelial cell lines have demonstrated that apelin-13 has angiogenic activity [18,19]. Many animal studies and a small number of human studies have demonstrated that apelin-13 is associated with the occurrence of ROP [7][8][9]. Thus, systemic apelin-13 and VEGF may be meaningful biomarkers to aid in the diagnosis of ROP [9,20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may play an important role in pathological retinal neovascularisation and affect the occurrence and development of ROP. However, few in vivo studies have analyzed the relationship between ROP and systemic apelin-13 concentrations [9]. Moreover, the relationship between apelin-13 and VEGF is unclear.…”
Section: Introductionmentioning
confidence: 99%